Oral Bioavailability Enhancement Of Poorly Soluble And Poorly Permeable Drugs Using Self-Microemulsifying Drug Delivery Systems And The Effect Of Piperine - Chitneni , Mallikarjun (2010)
There are approximately 40% of new drug molecules discovered and some drugmolecules that are available in the market, having poor bioavailability due to poorsolubility and/or poor permeability. The present study aimed at formulating a selfmicroemulsifying drug delivery system (SMEDDS) using two BCS class IV drugs, namely sulpiride and norfloxacin. Sulpiride is a P-gp substrate and norfloxacin is a substrate of MRP2, BCRP and an unknown efflux pump.